Migrações de idosos de São Paulo para Minas Gerais nas décadas de 1980 e 1990 - Marden Barbosa de Campos (2010)
This dissertation investigates the patterns and characteristics of elderly migrants from São Paulo to Minas Gerais in the 1980s and 1990s. This is an important research topic given the lack of studies on elderly migration in Brazil. This population subgroup, defined here as one comprisng indivuals 60 years old or more, does not migrate predominantly motivated by the search for employment and better wages (characteristic of younger migrants) but also by other factors such as seeking support and family reunion. Migration theories have, as a rule, been constructed from migration patterns of younger populations.The main hypothesis is that transitions occurring along the life cycle are also associated with the migration of the elderly in Brazil and, given the heterogeneity within this subgroup, it is important to identify and characterize distinct profiles of elderly migrants. These profiles are defined by factors such as retirement, physical and mental disability, widowhood, in addition to family issues such as household structure and the desire to reside with their children and relatives. We found that these factors affect elderly migration in our study in a similar fashion to what is observed in developed countries. However, some of them had specific features, such as retirement and condition of economic activity. In Brazil, one must consider that some retired people still work and, therefore, also migrate in search of better working conditions and pay. In order to construct the profiles we used a methodology knwon as Grade of Membership - GoM, and data from the National Census of 1991 and 2000. The GoM is a multivariate technique that aims to simplify the interpretation of a phenomenon through the creation of profiles that summarize the relationship of a set of variables on each element of the sample. Unlike most clustering methods, it is not considered that the elements are organized into well defined proflies, i.e. that an observation belongs or does not belong to a group with certain attributes. The GoM outlines extreme profiles of individuals and determine degrees of membership of each individual in relation to such profiles. The extreme profiles are generated from the association not observed among the variables and represent the most frequent types in the population. These profiles are reference groups that, in general, contain unique characteristics in the population. Due to the heterogeneity of the sample, most individuals differ in some degree of "pure types". From the degree of membership of each element of the sample to extremes profiles, we can create "mixed types" of individuals, representing more accurately the heterogeneity of the sample. An exploratory analysis was made, prior to the design of profiles, to understand the behavior of each variable as a basis to build the model.The profiles show that the size and heterogeneity of elderly migrants was growing between the 1980s and 1990s. In the 1980s there were three profiles of elderly migrants, with half of them being women seeking family reunification and support, and the other two profiles being comprised of men still economically active. In the 1990s, while working men continue to represent nearly half of the migrants, we found new profiles of women migrants, in addition to the women that migrated seeking support and family reunion. These new profiles were characteristic of women migrating to accompany spouses and other family members. Based on the profiles of elderly migrants, we can infer that there is a divide between movements typically "voluntary" and others, typically "necessary." The profiles of younger and wealthier migrants, who lived alone or with a spouse and who were still economically active, approach the first type of movement, "voluntary migration". The profiles of older people, widows, poor and that lived in the house of their children, are closer to the other type, migration of "necessity".It is also important to consider that the consolidation of the demographic transition in the coming decades and population aging in Brazil, elderly migration may become an important issue as well as its impact on families, labor market and health and welfare institutions, both at the places of origin and destination of migration.